Effects of adjunctive zonisamide treatment on weight and body mass index in children with partial epilepsy. (6th February 2015) - Lagae, L.; Meshram, C.; Giorgi, L.; Patten, A.
<x xml:space="preserve">Abstract</x> Background Zonisamide has been associated with weight loss in children and adults. Aims of the study To assess the effects of adjunctive zonisamide on weight and body mass index (BMI) in children with partial epilepsy. Methods A subanalysis was conducted of a Phase III trial and extension study, in which children with partial epilepsy received adjunctive zonisamide (target dose 8 mg/kg/day; maximum 500 mg/day). Changes in weight were correlated with skeletal development and sexual maturation. Results Overall, 179 children (93 male, 86 female; age 6–18 years) received zonisamide (mean duration 370.6 days). Weight loss ≥5% was reported for 64 of 179 (35.8%) zonisamide‐treated children. Of these, 46.9% were overweight/obese at study entry, compared with 23.4% at study end (P = 0.0007); 48.4% had normal weight at study entry, compared with 65.6% at study end (P = 0.03). Three patients were underweight at study entry, and four more became underweight by study end. No consistent correlations between weight loss and skeletal development or sexual maturation were observed. Conclusions Approximately one‐third of children treated with zonisamide experienced ≥5% weight loss. Weight loss was most apparent in children with high baseline BMI values and did not appear to be associated with any consistent effects on growth and development.